2022
DOI: 10.1177/14759217221076736
|View full text |Cite
|
Sign up to set email alerts
|

Damage severity assessment in composite structures using multi-frequency lamb waves

Abstract: When a narrowband tone burst excitation signal is used to generate Lamb waves in the thin composite plates, a suitable frequency of the excitation signal is typically chosen to excite a solitary mode of Lamb wave in the structure. However, if and as the damage severity changes in the structure, it may be possible that the frequency of the excitation signal may influence the response metric. In the present work, the use of a chirp signal as an excitation signal for damage severity assessment is proposed. The us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The structural health-monitoring method based on piezoelectric sensing array excites and receives guided wave signals online through piezoelectric devices integrated inside or on the surface of the structure, and identifies the structural damage state based on the change in the guided wave signal characteristics [6,7], but it requires a large number of signal transmission cables, which is inclined to cause complexity of the monitoring system, and there are certain limitations in monitoring structural damage at large scales. In contrast, distributed fiber optic sensors have unique advantages such as resistance to electromagnetic and radio frequency interference, integration of transmission and sensing, and good applicability for real time monitoring of spacecraft structural damage [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The structural health-monitoring method based on piezoelectric sensing array excites and receives guided wave signals online through piezoelectric devices integrated inside or on the surface of the structure, and identifies the structural damage state based on the change in the guided wave signal characteristics [6,7], but it requires a large number of signal transmission cables, which is inclined to cause complexity of the monitoring system, and there are certain limitations in monitoring structural damage at large scales. In contrast, distributed fiber optic sensors have unique advantages such as resistance to electromagnetic and radio frequency interference, integration of transmission and sensing, and good applicability for real time monitoring of spacecraft structural damage [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the appropriate excitation frequency was determined, the reflection coefficients of narrowband ultrasonic waves in a notch still exhibit a cosinusoidal periodic shape [28], which means that the damage index based on narrowband excitation may be non-monotonic with the increase of damage. To tackle this problem, Nandyala et al [29] utilized broadband chirp signal as excitation and defined the decorrelation coefficient as the damage index based on chirp response in time domain. The results demonstrated that the damage index could reflect the cumulative effect of multiple frequencies and exhibit monotonic trends with the development of damage.…”
Section: Introductionmentioning
confidence: 99%
“…The chirp excitation-based narrowband signal reconstruction method has been used to select the optimal excitation frequency [25], achieve steady damage monitoring [29] and improve the damage localization accuracy [32,33], demonstrating the superiority of chirp excitation in ultrasonic wavebased structural health monitoring. The multiple-frequency components contained in the broadband chirp response possess different sensitivities to different bolt tightness conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Dafydd and Khodaei 27 used laser Doppler vibrometer to capture wavefield interaction via ultrasonic guided Lamb waves to characterize the through thickness severity in carbon-fibre-reinforced polymer structures. Later, Nandyala et al 28 extended the usage of multi-frequency lamb waves to quantify delamination in composite plates. Cheng et al 29 used output-only signals to establish relationships of damage severity with low-frequency components and showed its applicability on simple multi-degree-of-freedom (DoF) spring-mass system.…”
Section: Introductionmentioning
confidence: 99%